An ingestible bioimpedance sensing device for wireless monitoring of epithelial barriers - Brian M. Holt; Justin M. Stine; Luke A. Beardslee; Hammed Ayansola; Younggeon Jin; Pankaj J. Pasricha; Reza Ghodssi (Microsystems & Nanoengineering)
Abstract Existing gastrointestinal (GI) diagnostic tools are unable to non-invasively monitor mucosal tight junction integrity in vivo beyond the esophagus. In the GI tract, local inflammatory processes induce alterations in tight junction proteins, enhancing paracellular ion permeability. Although transepithelial electrical resistance (TEER) may be used in the laboratory to assess mucosal barrier integrity, there are no existing methodologies for characterizing tight junction dilation in vivo. Addressing this technology gap, intraluminal bioimpedance sensing may be employed as a localized, non-invasive surrogate to TEER electrodes used in cell cultures. Thus far, bioimpedance has only been implemented in esophagogastroduodenoscopy (EGD) due to the need for external electronics connections. In this work, we develop a novel, noise-resilient Bluetooth-enabled ingestible device for the continuous, non-invasive measurement of intestinal mucosal “leakiness.” As a proof-of-concept, we validate wireless impedance readout on excised porcine tissues in motion. Through an animal study, we demonstrate how the device exhibits altered impedance response to tight junction dilation induced on mice colonic tissue through calcium-chelator exposure. Device measurements are validated using standard benchtop methods for assessing mucosal permeability.